Establishing the identity of persons - Ene, Ramona-Madalina (Eximia, 2023)
Establishing the identity of persons is a predominant police method with a preventive character, intended to combat both possible crimes, but also to discover delinquents. Establishing the identity involves checking the documents provided with a photo of both Romanian citizens and foreigners who enter our country or are in transit. More and more often, the identity of people is established when crossing state borders, thus the state of danger can be removed. We can say that the procedure of establishing the identity is a measure that the judicial bodies resort to, and with the help of witnesses or victims, they establish the identity of people with the help of technical methods. Throughout life, both the Romanian Constitution and the Criminal Code have tried to diversify and improve identification methods, to be as simple as possible and to reach the best possible result in the shortest possible time with the aim of reducing the criminal phenomenon . In the theme we chose to write the establishment of the identity of the persons, the stages of this process, the persons subject to identification, but also the circumstances in which this process is carried out. We will detail the cases in which establishing identification is possible and under what conditions, but especially the presentation of the 3 cases through which establishing identity is possible, establishing identity through portrait photography, through voice signals, but not least through external signals.